Pengaruh Lokasi, Harga, dan Citra Merek Terhadap Loyalitas Pelanggan Point Coffee Di Indomaret S. Parman Waru Sidoarjo - Maulana, Alfian Reza; Suyono, Suyono (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Customer loyalty is the main key in supporting company growth because loyal customers tend to choose to return to buy products regularly. The aim of this research is to prove and analyze the influence of location, price and brand image on customer loyalty. The research population is Point Coffee customers at Indomaret S. Parman Waru Sidoarjo whose number is not known with certainty (infinite) because there is no recording of the exact number. Based on a simple random sampling technique, the research sample was taken from 100 Point Coffee customers at Indomaret S. Parman Waru Sidoarjo who the researchers met when distributing the questionnaire. The data analysis technique uses multiple linear regression analysis, coefficient of determination, t test and F test. The conclusion of this research is that location influences customer loyalty. Price influences customer loyalty. Brand image influences customer loyalty. Location, price and brand image simultaneously influence customer loyalty. This shows that Point Coffee customer loyalty at Indomaret S. Parman Waru Sidoarjo is influenced by strategic location, Point Coffee prices, as well as Point Coffee's good brand image in the community.